Advanced IMS multipoint conference management using web services. - Gomez, Miguel; de Miguel, Tomas P.
The IMS conference control interfaces are still in an early stage of development, allowing only the creation of basic group communication services where the service definition and policy are either preconfigured or managed through proprietary mechanisms. The Web service abstraction for third-party service application development of those native interfaces, the OSA Parlay X multimedia conference Web service, inherits these limitations, therefore constraining the possibilities for advanced multipoint conferencing application deployment over the IMS platform. In order to address these deficiencies, the native IMS conference control interfaces need to be enhanced to provide a broader and finer-grained management environment, while maintaining high flexibility, scalability, and interoperability levels. This article describes the current IMS conferencing framework, at both the native and application-interfacing levels, analyzing its deficiencies and presenting how a deeper involvement of Web services would contribute to overcoming its limitations at both levels.
Keywords: IMS conference control interfaces; IMS multipoint conference management; Web service abstraction; Application-interfacing levels; Group communication services; Interoperability levels